Klinik Eduprenuership Berbasis Life Skill Program 5.0 : Upaya Peningkatan Minat Berwirausaha pada Siswa di Zona Terisolir-Kalimantan Barat - Permatasari, Rindah; Tirsa, Aprima (Institute for Research and Community Service (LPPM) of the Islamic University of Jember, 2024)
Edupreunership Clinic Based on Life Skill Program5.0 at SMA N 1 Pinoh Utara aims to measure Student Entrepreneurial Interest and student Life Skills integrated in Eduprenuership. Activities consist of preparation, The implementation of community service is carried out with a method that is planned and designed according to the characteristics and needs of the fostered partners. Implementation and Evaluation. The excellence of this program lies in efforts to increase partners' knowledge, interest and skills in entrepreneurship which consists of the planning stage, product manufacturing to the marketing process of business products. The results of the activity show that there is a significant increase before and after the implementation of eduprenuership training activities in the form of increased interest, knowledge and entrepreneurial skills of students. Overall, this program intends to create an entrepreneurial culture for high school students so that it can produce a generation of creative and innovative entrepreneurs and can collaborate with local industries and financial institutions so as to help students understand market needs and financial resources.